2017
DOI: 10.3178/hrl.11.85
|View full text |Cite
|
Sign up to set email alerts
|

Impact of temperature changes on groundwater levels and irrigation costs in a groundwater-dependent agricultural region in Northwest Bangladesh

Abstract: Abstract:Changes in hydrological processes due to rising temperatures and related effects on the socio-economy and people's livelihood are major concerns in Bangladesh. A study has been performed to assess the effects of increasing temperature on the groundwater levels and consequent changes in irrigation costs for groundwater-dependent irrigated agriculture in Northwest Bangladesh. A support vector machine (SVM) was used to model the temporal variations in groundwater level from rainfall, evapotranspiration, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
(26 reference statements)
0
16
0
1
Order By: Relevance
“…Consequently, any decline in the water table, due to changes in precipitation patterns and rises in temperature, can reduce well yield and increase pumping costs. This could well have a serious economic impact on the livelihood of farmers in the regions where groundwater is used as the major source of irrigation [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, any decline in the water table, due to changes in precipitation patterns and rises in temperature, can reduce well yield and increase pumping costs. This could well have a serious economic impact on the livelihood of farmers in the regions where groundwater is used as the major source of irrigation [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is projected to reduce groundwater resources significantly in most dry subtropical regions. In a groundwater-dependent irrigated region in northwest Bangladesh, the average groundwater level during the major irrigation period (January-April) is projected to decrease in accordance with temperature rise (Salem et al, 2017). Agroforestry has potential for improving water use efficiency by reducing the unproductive components of the water balance, i.e.…”
Section: Water (Quality and Quantity)mentioning
confidence: 99%
“…Döll [55] reported that the densely populated south Asian region is highly sensitive to the decreases in groundwater recharge due to climate change because of the high dependency on groundwater. Saleh et al [56] found that average groundwater level during the pre-monsoon irrigation period decreased by 0.15-2.01 m due to an increase in temperature of 1.0-5.0 • C. Modeling groundwater level under general circulation model revealed that groundwater levels in Northwest Bangladesh would drop by only 0.18 to 0.45 m, under a 1.5 • C temperature rise scenario [57]. This indicates that climate change will aggravate the existing condition of water scarcity in the region.…”
Section: Water Scarcity In Northwest Bangladeshmentioning
confidence: 99%